2020
DOI: 10.3390/v12121458
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, Rapamycin and Metformin as Modulators of Antiviral Pathways

Abstract: Balanced nutrition and appropriate dietary interventions are fundamental in the prevention and management of viral infections. Additionally, accurate modulation of the inflammatory response is necessary to achieve an adequate antiviral immune response. Many studies, both in vitro with mammalian cells and in vivo with small animal models, have highlighted the antiviral properties of resveratrol, rapamycin and metformin. The current review outlines the mechanisms of action of these three important compounds on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 199 publications
0
12
0
Order By: Relevance
“…Resveratrol has shown antiviral activity against several viruses, such as polyomavirus, influenza virus, respiratory syncytial virus, MERS-CoV, and the emerging SARS-CoV [61]. The mechanisms of action of three important compounds (resveratrol, rapamycin, and metformin) on the cellular pathways involved in viral replication and the mechanisms of virus-related diseases, as well as the current status of their clinical use, were discussed [62]. The antiviral effect of resveratrol against MERS-CoV was evaluated through antiapoptotic and viral titer assays.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol has shown antiviral activity against several viruses, such as polyomavirus, influenza virus, respiratory syncytial virus, MERS-CoV, and the emerging SARS-CoV [61]. The mechanisms of action of three important compounds (resveratrol, rapamycin, and metformin) on the cellular pathways involved in viral replication and the mechanisms of virus-related diseases, as well as the current status of their clinical use, were discussed [62]. The antiviral effect of resveratrol against MERS-CoV was evaluated through antiapoptotic and viral titer assays.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first, to our knowledge, evaluation among patients utilizing metformin documenting an influenza treatment response. Our research selected and evaluated metformin based upon preclinical data [7,9,17]. Specifically, published data suggest that an alteration in the metabolic profile of T cells in individuals with obesity impairs the activation of the adaptive immune cells [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have stressed the antiviral functions of resveratrol both in vivo and in vitro ( 132 ). Xu et al ( 100 ) has revealed that resveratrol alleviates duck viral enteritis (an acute, contagious and herpesvirus infection of poultry intestine) through suppressing the multiplication of duck enteritis virus in host cells.…”
Section: Resveratrol and Intestinal Diseasesmentioning
confidence: 99%